Open Science, Open Data, and Open Scholarship: European Policies to Make Science Fit for the Twenty-First Century - Burgelman, Jean-Claude; Pascu, Corina; Szkuta, Katarzyna; Von Schomberg, Rene; Karalopoulos, Athanasios; Repanas, Konstantinos; Schouppe, Michel (Frontiers in Big Data, 2019)
Open science will make science more efficient, reliable, and responsive to societal challenges. The European Commission has sought to advance open science policy from its inception in a holistic and integrated way, covering all aspects of the research cycle from scientific discovery and review to sharing knowledge, publishing, and outreach. We present the steps taken with a forward-looking perspective on the challenges laying ahead, in particular the necessary change of the rewards and incentives system for researchers (for which various actors are co-responsible and which goes beyond the mandate of the European Commission). Finally, we discuss the role of artificial intelligence (AI) within an open science perspective.